Threat modeling of a multi-UAV system. (December 2020) - Almulhem, Ahmad
Abstract: As Multi-UAV systems are still in early design stages, threat modeling can play a crucial role in attaining the "secure by design" notion in such complex cyber-physical systems (CPS). In this paper, we employ a threat modeling methodology, known as threat trees to analyze and enumerate threats impacting the Internet of Drones (IoD) architecture. The proposed threat tree is meant to provide a holistic perspective of threats impacting an IoD system.